One-Time Password System with Infinite Nested Hash Chains - Eldefrawy, Mohamed Hamdy; Khan, Muhammad Khurram; Alghathbar, Khaled (Security Technology, Disaster Recovery and Business Continuity, 2010)
Hash chains have been used as OTP generators. Lamport hashes have an intensive computation cost and a chain length restriction. A solution for signature chains addressed this by involving public key techniques, which increased the average computation cost. Although a later idea reduced the user computation by sharing it with the host, it couldn’t overcome the length limitation. The scheme proposed by Chefranov to eliminate the length restriction had a deficiency in the communication cost overhead. We here present an algorithm that overcomes all of these shortcomings by involving two different nested hash chains: one dedicated to seed updating and the other used for OTP production. Our algorithm provides forward and non-restricted OTP generation. We propose a random challenge–response operation mode. We analyze our proposal from the viewpoint of security and performance compared with the other algorithms.